Leverage. The final season [5] [videorecording (DVD)]. - Hutton, Timothy, 1960-; Riesgraf, Beth; Hodge, Aldis; Williams, Treat; Elwes, Cary, 1962- (20th Century Fox Home Entertainment, 2013)
"Leverage focuses on a team led by former insurance investigator turned thief, Nate Ford ... . Together, they try to level the playing field for people whose lives have been destroyed by the rich and powerful. In the final season of Leverage, the team will be forced to face changing personal dynamics as the relationship between Parker ... and Hardison ... heats up, and Nate continues to struggle with inner demons"--Container.